CEO Compensation and SMEs Performance: A Structural Equation Modelling Approach from Jordanian Listed SMEs - Hamada Alkhuzaie, Abbas Saad; Mansour, Alaa Zuhair; Altarawneh, Marwan; Elfedawy, Alya (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This study’s main goal is to discover whether the CEO’s cash comparison affects SMEs’ performance, with the bonus having a favorable impact instead. The research comprises an analysis of the SMEs mentioned in the Jordanian Ministry of Industry and Trade. To test hypotheses, data were meticulously collected from a sample of 80 SMEs in Amman, Jordan, a pivotal business hub in the country. Utilizing Structural Equation Modelling through Smart PLS 3, our chosen methodological framework facilitated a comprehensive analysis of the intricate relationships between CEO compensation variables and SME performance. The study’s conclusions show a substantial correlation between the performance of SMEs included and the components of CEO compensation in the Jordanian Ministry of Industry and Trade. Despite this, it has been discovered that a few additional incentive factors significantly improve performance in SMEs. This study has shown that some incentive contract theories are appropriate for businesses with specific sizes and operating in particular industries.